Change management practices and counterproductive work behavior among South African academics: does gender matter? - Chipunza, Crispen; Radebe, Patrick (Frontiers in Education, 2025)
Globally, higher education institutions are continuously involved in change in response to advances in digital technology, geopolitics, population dynamics, gender mainstreaming, and climate change. At the same time, reports of counterproductive work behavior among academics are alarming. The alarming rates have raised concerns on whether the change management practices adopted by university management in institutions of higher education learning can explain these academic behaviors. The change management practices will likely have an impact on academics' behavior. However, to date, without empirical evidence, this remains speculative. The purpose of this paper was therefore to establish the relationship between change management practices and counterproductive work behavior of academics, and whether gender moderates this relationship. Quantitative data were collected from academics at a selected higher education institution in South Africa, and the final sample was 129. The findings showed a statistically significant correlation between change management practices and counterproductive work behaviors. Gender moderates the relationship between change management practices and interpersonal counterproductive work behavior. The study contributes to existing literature on change management and counterproductive work behavior in higher education. The findings are practically relevant for enhancing gender sensitivity during the process of change among academics and elsewhere.